2009
DOI: 10.1186/1477-7819-7-87
|View full text |Cite
|
Sign up to set email alerts
|

Relapse in resected lung cancer revisited: does intensified follow up really matter? A prospective study

Abstract: Backgroundbeside the well known predominance of distant vs. loco-regional relapse, several aspects of the relapse pattern still have not been fully elucidated.Methodsprospective, controlled study on 88 patients operated for non-small cell lung cancer (NSCLC) in a 15 months period. Stage IIIA existed in 35(39.8%) patients, whilst stages IB, IIA and IIB existed in 10.2%, 4.5% and 45.5% patients respectively. Inclusion criteria: stage I-IIIA, complete resection, systematic lymphadenectomy with at least 6 lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(23 reference statements)
1
10
0
1
Order By: Relevance
“…From literature review, Subotic et al [ 28 ] stated that the intensified follow up did not increase either the proportion of patients detected with asymptomatic relapse or the number of patients with specific oncological treatment of relapse. However, the above follow-up method was regular monthly telephone contact with patients and/or their families in order to get reliable information about the patient’s general condition and eventual new complaints that were not present on discharge.…”
Section: Discussionmentioning
confidence: 99%
“…From literature review, Subotic et al [ 28 ] stated that the intensified follow up did not increase either the proportion of patients detected with asymptomatic relapse or the number of patients with specific oncological treatment of relapse. However, the above follow-up method was regular monthly telephone contact with patients and/or their families in order to get reliable information about the patient’s general condition and eventual new complaints that were not present on discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, there were no scheduled radiological follow-up reported. 32 There were no suitable surveillance studies available for analysis reliant on PROMs or biomarkers. Intended duration of follow-up was 2 years, 33,34 5 years, [35][36][37] ongoing, 38 or undefined.…”
Section: Resultsmentioning
confidence: 99%
“…Brain and bones are the most common sites of relapse in lung cancer after adjuvant treatment 2. The most important risk factors for the relapsing disease are positive lymph nodes and high-grade (poor differentiated) tumours 4…”
Section: Discussionmentioning
confidence: 99%
“…In spite of advances in surgical techniques, the 5-year survival for stage IB lung cancer is 60% 1. Common sites of distant relapse in lung cancer after surgery are brain (51.4%), bone (18.9%), liver and contralateral lung (16.2% each) 2. There have been a very few cases of relapse in pancreas.…”
Section: Introductionmentioning
confidence: 99%